Sastra (Puisi) Sebagai Kebudayaan Bangsa Arab - Moch Yunus (Institut Ilmu Keislaman Zainul Hasan Genggong, 2015)
Arab community life can be seen in the literature which become the product of that era, especially in the case of syi'ir. Arab syi'ir uniqueness can be seen through the perspective of reception, as it pertains to the historical and aesthetic aspects. Historical aspects related to the birth of the pre-Islamic Arabic poetry and development until modern times. Aspects related to the aesthetic beauty of the Arabic used in syi'ir of Arab. Aesthetics basic in understanding the understanding the Arabic poetry of pre-Islamic times to the modern era is through the reception theory, meaning that through literature diachronic. Model of this literature focuses on the issue of how the Arabic literature into Arabic literature mirror society and become autonomous in the world. Ideally, literature synchronic and diachronic literature can be combined in a literary historical coherence, and further productively understood as a social process or as the moment the development of Arabic literature